2018
DOI: 10.25304/rlt.v26.2140
|View full text |Cite
|
Sign up to set email alerts
|

Learning in virtual reality: Effects on performance, emotion and engagement

Abstract: Recent advances in virtual reality (VR) technology allow for potential learning and education applications. For this study, 99 participants were assigned to one of three learning conditions: traditional (textbook style), VR and video (a passive control). The learning materials used the same text and 3D model for all conditions. Each participant was given a knowledge test before and after learning. Participants in the traditional and VR conditions had improved overall performance (i.e. learning, including knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
190
4
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(222 citation statements)
references
References 25 publications
15
190
4
13
Order By: Relevance
“…The results of this study concur with those reported by Devon [49], which indicated that VR exerted a notable effect on emotion. Participants became more active in their learning, and their negative emotions decreased.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study concur with those reported by Devon [49], which indicated that VR exerted a notable effect on emotion. Participants became more active in their learning, and their negative emotions decreased.…”
Section: Discussionsupporting
confidence: 93%
“…Although I-VR has been shown to confer a benefit in science education, there is evidence to suggest that not all learning objectives can be learned equally well. For instance, in task devised by Allcoat and von Mühlenen (2018), the researchers found that I-VR conferred a benefit over video or textbook learning when questions required remembering, but not ones pertaining to understanding of the material. The authors suggest that unfamiliarity and the novelty of the I-VR environments could have contributed to the lack of an obvious benefit in the latter domain.…”
Section: Science Based Cognitive Studiesmentioning
confidence: 99%
“…The number of evidence-based studies about this innovation are, however, low in number. Examples where VR has led to an increase in either attainment or preparedness in students include Bellamy and Warren (2011), Webster (2015) and Allcoat and von Mühlenen (2018). Of these studies, the number of students experiencing VR are small (Webster = 25 and Allcat and von Mühlenen = 33), the same is true for this study.…”
Section: The Technologymentioning
confidence: 54%